The Absorption of Recent Graduates into the Australian Labour Market: Variations by University Attended and Field of Study - Li, I.; Miller, Paul (Wiley-Blackwell Publishing Asia, 2013)
This study uses data from the 1999 to 2009 Graduate Destination Surveys to investigate the absorption of recent university graduates into the Australian labour market. The results indicate that graduates of the Group of Eight and Australian Technology Network are less likely than graduates of other universities to be employed in jobs that do not require their qualification. No university group, however, has a clear advantage in protecting its graduates from the adverse earnings consequences associated with working in such jobs. Field of study plays an important role in determining both whether graduates work in occupations that require their qualification and earnings.